2019
DOI: 10.3174/ajnr.a6256
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Analysis of Postoperative Rupture of Unruptured Intracranial Aneurysms after Placement of Flow-Diverting Stents: A Matched Case-Control Study

Abstract: BACKGROUND AND PURPOSE: Postoperative rupture of intracranial aneurysm has been reported as a fatal complication after flow-diverter placement. We assessed several hemodynamic variables to explore risk factors in the postoperative rupture process. MATERIALS AND METHODS:We enrolled 10 patients with intracranial aneurysms, treated with flow diverters between September 2014 and December 2018, who experienced postoperative aneurysm rupture (postoperative aneurysm rupture group). We matched these subjects 1:2 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…26 Li et al. 13 found that hemodynamics played an important role in postoperative aneurysm rupture after flow diversion, and thus we speculated that hemodynamic factors might also play an important role in the process of DIPH occurrence.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…26 Li et al. 13 found that hemodynamics played an important role in postoperative aneurysm rupture after flow diversion, and thus we speculated that hemodynamic factors might also play an important role in the process of DIPH occurrence.…”
Section: Discussionmentioning
confidence: 80%
“…PSM is a recognized method of balancing covariates in two groups to reduce selection bias. 13 All quantitative hemodynamic parameters were presented as means and standard deviations. For qualitative data, the χ2 test or the Fisher’s exact test was used to compare the differences between two groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we also compared the EL of aneurysm sac calculated by the two methods ( Figure 8B ). In previous studies in which the Bernoulli equation–based method was applied ( 6 , 12 , 14 17 ), the EL of aneurysm sac (EL beAN ) was characterized by the EL changes caused by the aneurysm formation, namely, the difference of EL be between with-aneurysm and non-aneurysm models. In our method, the EL of aneurysm sac (EL dfAN ) can be obtained by integrating DF over aneurysmal domain.…”
Section: Resultsmentioning
confidence: 99%
“…Some suggest that altered hemodynamics induced by the flow diverter increases the wall stress to the aneurysm. 29 Others favor the theory that thrombus formed in the aneurysm releases enzymes that cause lysis of the aneurysm wall.…”
Section: Discussionmentioning
confidence: 99%